Persistent Bacteremia from Pseudomonas aeruginosa with In Vitro Resistance to the Novel Antibiotics Ceftolozane-Tazobactam and Ceftazidime-Avibactam - Louie Mar Gangcuangco; Patricia Clark; Cynthia Stewart; Goran Miljkovic; Zane K. Saul (Case Reports in Infectious Diseases)
Ceftazidime-avibactam and ceftolozane-tazobactam are new antimicrobials with activity against multidrug-resistant Pseudomonas aeruginosa. We present the first case of persistent P. aeruginosa bacteremia with in vitro resistance to these novel antimicrobials. A 68-year-old man with newly diagnosed follicular lymphoma was admitted to the medical intensive care unit for sepsis and right lower extremity cellulitis. The patient was placed empirically on vancomycin and piperacillin-tazobactam. Blood cultures from Day 1 of hospitalization grew P. aeruginosa susceptible to piperacillin-tazobactam and cefepime identified using VITEK 2 (Biomerieux, Lenexa, KS). Repeat blood cultures from Day 5 grew P. aeruginosa resistant to all cephalosporins, as well as to meropenem by Day 10. Susceptibility testing performed by measuring minimum inhibitory concentration by E-test (Biomerieux, Lenexa, KS) revealed that blood cultures from Day 10 were resistant to ceftazidime-avibactam and ceftolozane-tazobactam. The Verigene Blood Culture-Gram-Negative (BC-GN) microarray-based assay (Nanosphere, Inc., Northbrook, IL) was used to investigate underlying resistance mechanism in the P. aeruginosa isolate but CTX-M, KPC, NDM, VIM, IMP, and OXA gene were not detected. This case report highlights the well-documented phenomenon of antimicrobial resistance development in P. aeruginosa even during the course of appropriate antibiotic therapy. In the era of increasing multidrug-resistant organisms, routine susceptibility testing of P. aeruginosa to ceftazidime-avibactam and ceftolozane-tazobactam is warranted. Emerging resistance mechanisms to these novel antibiotics need to be further investigated.